Conductivity structure of the lithosphere‐asthenosphere boundary beneath the eastern North American margin. (25th February 2017) - Attias, Eric; Evans, Rob. L.; Naif, Samer; Elsenbeck, Jimmy; Key, Kerry
Abstract: Tectonic plate motion and mantle dynamics processes are heavily influenced by the characteristics of the lithosphere‐asthenosphere boundary (LAB), yet this boundary remains enigmatic regarding its properties and geometry. The processes involved in rifting at passive margins result in substantial alteration of the lithosphere through the transition from continental to oceanic lithologies. Here we employ marine magnetotelluric (MT) data acquired along a ∼135 km long profile, offshore Martha's Vineyard, New England, USA, to image the electrical conductivity structure beneath the New England continental margin for the first time. We invert the data using two different MT 2‐D inversion algorithms and present a series of models that are obtained using three different parameterizations: fully unconstrained, unconstrained with an imposed LAB discontinuity and a priori constrained lithosphere resistivity. This suite of models infers variability in the depth of the LAB, with an average depth of 115 km at the eastern North America passive margin. Models robustly detect a ∼350 Ωm lithospheric anomalous conductivity zone (LACZ) that extends vertically through the entire lithosphere. Our preferred conductivity model is consistent with regional P ‐to‐S receiver function data, shear‐wave velocity, gravity anomalies, and prominent geological features. We propose that the LACZ is indicative of paleolithospheric thinning, either resulting from kimberlite intrusions associated with rifting and the New England Great Meteor hot spot track, or from shear‐driven localized deformation related to rifting. Key Points: LAB topography varies between ∼85 and 145 km depth A thin lithosphere is associated with a zone of anomalous conductivity The lithospheric anomalous conductivity zone (LACZ) possibly results from kimberlite intrusions or alteration in rheology due to localized rift‐related deformation